Flexible and Robust Ti3C2Tx/(ANF@FeNi) Composite Films with Outstanding Electromagnetic Interference Shielding and Electrothermal Conversion Performances. Issue 10 (6th September 2022) - Zhao, Bo; Ma, Zhonglei; Sun, Yuyao; Han, Yixuan; Gu, Junwei
Abstract : Flexible and robust multifunctional electromagnetic interference (EMI) shielding materials are playing an increasingly important role in areas of aerospace, electronic communication, artificial intelligence, and wearable electronic devices. Herein, the magnetic and conductive Ti3 C2 T x /(ANF@FeNi) EMI shielding composite films are fabricated via in situ growth and vacuum‐assisted filtration methods. The introduction of magnetic FeNi nanoparticles can effectively enhance the electromagnetic recombination losses, leading to improved EMI shielding effectiveness (EMI SE) of the composite films. The obtained Ti3 C2 T x /(ANF@FeNi) composite films show excellent EMI shielding and electrothermal conversion performances. When the mass fraction of Ti3 C2 T x and FeNi fillers is 60 wt% and their mass ratio is 4:1, the EMI SE of the composite films (50 μm) reaches 60.7 dB in the X‐band (8.2–12.4 GHz). When a low voltage of 3 V is applied, the surface heating temperature of the composite films quickly reaches 111.2 °C. Moreover, the composite films possess satisfied long‐term heating stability under the constant applied voltage. In addition, the composite films exhibit excellent thermal conductivity and mechanical properties. The thermal conductivity ( λ ) and thermal diffusivity ( α ) reach 4.72 W m −1 K −1 and 4.36 mm 2 s −1, respectively, and the tensile strength and tensile modulus reach 113.4 MPa and 3.1 GPa, respectively. Abstract : The magnetic and conductive electromagnetic interference (EMI) shielding composite films are fabricated by the in situ growth and vacuum‐assisted filtration methods. The resultant composite films exhibit excellent EMI shielding performances and electrothermal conversion properties, as well as outstanding thermal stability, thermal conductivity, and mechanical properties, showing important application prospects in EMI shielding and thermal management systems in various areas.